Snow Thickness and Brightness Temperature on Multi-Year Ice. - Lohanick,A W (1982)
The 33 GHz brightness temperature (Tb) of a 40-meter strip of multi-year ice was obtained using a sled-mounted radiometer. Snow accumulations along the strip varied from 0 to 40 cm. After the snow was removed, Tb was re-measured. Detailed comparisons of snow depth vs. change in Tb show that snow thickness or snow water equivalent alone are not sufficient to describe the emissivity of the snow pack. (Author)